-(v-4.1)=-2.1v-0.1(1+v)

Simple and best practice solution for -(v-4.1)=-2.1v-0.1(1+v) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(v-4.1)=-2.1v-0.1(1+v) equation:



-(v-4.1)=-2.1v-0.1(1+v)
We move all terms to the left:
-(v-4.1)-(-2.1v-0.1(1+v))=0
We add all the numbers together, and all the variables
-(v-4.1)-(-2.1v-0.1(v+1))=0
We get rid of parentheses
-v-(-2.1v-0.1(v+1))+4.1=0
We calculate terms in parentheses: -(-2.1v-0.1(v+1)), so:
-2.1v-0.1(v+1)
We multiply parentheses
-2.1v-0.1v-0.1
We add all the numbers together, and all the variables
-2.2v-0.1
Back to the equation:
-(-2.2v-0.1)
We add all the numbers together, and all the variables
-1v-(-2.2v-0.1)+4.1=0
We get rid of parentheses
-1v+2.2v+0.1+4.1=0
We add all the numbers together, and all the variables
1.2v+4.2=0
We move all terms containing v to the left, all other terms to the right
1.2v=-4.2
v=-4.2/1.2
v=-3+0.6/1.2

See similar equations:

| 28=n+2 | | 3.00+0.55x=6.00+0.35x | | 30x+6=12x+42 | | 2(8x-6)+2x=138 | | 6(x-12)=-606(x−12)=−60 | | 2x+5x-1=2x+3-7 | | z=-1+11z | | -4m-14=-28-6m | | (4x-5)(2+9x)=0 | | 96=6x^2 | | 19.00+1.90x=11.20+2.50x | | 3x(x+2)+4(x+2)=0 | | 80-2x=50-x | | 3^x=12x-9 | | x^2=9/625 | | 8-8=6-6(x+6)+3x | | 4+5x=16-x | | 5c-7-2c=30 | | 35-3n=8 | | 5(r+7)=-15 | | 180=(2x+41)+53 | | 10k+-9=9k+10 | | 1/10(x+50)-x+13=0 | | 3(3x-13)=4x-14 | | -x/4=-1.11 | | -16t^2+140t+4=0 | | 3x-16-x+6=0 | | 14=-8x-2 | | 2x^2+13x-132=0 | | 3x=2(x+6)+2(x+8) | | -16^2+140t+4=0 | | 8r-6+9r=31 |

Equations solver categories